Local Wisdom Becomes the Commander in Criminal Resolution - Andriyani, Andriyani; Dewi, Rusmala (Nurani, 2023)
Settlement of criminal cases through peaceful means is highly recommended, especially in minor criminal cases. This is important so that cases do not accumulate. This method is widely applied in customary law which prioritizes restorative justice. However, not all customs that exist in society can be accepted by Islamic law. Therefore, this research conducted a study of the "tepung tawar" custom that exists in the Ibul Village community. The research uses a qualitative type with a field research model. The data processed consists of primary, secondary and tertiary data. The research was conducted in Ibul Village, Belida Darat subdistrict. The results of the research reveal that in the tepung tawar tradition there is a very high element of forgiveness. This aims to ensure that there are no grudges between the disputing parties, so that they can continue to live peacefully side by side in society. In the Ibul village community, it is customary for "tepung tawar" to be the commander-in-chief in resolving criminal cases of abuse. There are no elements that conflict with Islamic law in this customary practice, so the "tepung tawar" custom is included in the al-‘urf al-shahihah category so it can be accepted as a legal basis.